1991
DOI: 10.1016/0378-1097(91)90181-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of a lacZ fusion to study transcriptional regulation of the Rhodobacter capsulatus hemA gene

Abstract: An EcoRI fragment containing the Rhodobacter capsulatus hemA promoter has been cloned into a lacZ translational fusion vector. The resulting plasmid produced a hemA-lacZ fusion protein with a molecular mass of 147,000. Expression of the hemA-lacZ fusion, as measured by production of beta-galactosidase, was regulated 2- to 3-fold by oxygen tension. The unexpectedly small change in beta-galactosidase levels suggests that transcriptional regulation of the hemA gene is not the major factor in oxygen-mediated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Aminolevulinate synthase activity in AJB529 was approximately 10% of that in PAS100, while the activities of the other two enzymes were the same in the two strains. The residual aminolevulinate synthase activity in AJB529 is most likely due to a small amount of transcription initiating within the Tn 5 in this strain (49). While R. sphaeroides has two hemA isozymes (hemA and hemT) (35), multiple studies suggest that R. capsulatus has only a single hemA isozyme (17,25,50).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Aminolevulinate synthase activity in AJB529 was approximately 10% of that in PAS100, while the activities of the other two enzymes were the same in the two strains. The residual aminolevulinate synthase activity in AJB529 is most likely due to a small amount of transcription initiating within the Tn 5 in this strain (49). While R. sphaeroides has two hemA isozymes (hemA and hemT) (35), multiple studies suggest that R. capsulatus has only a single hemA isozyme (17,25,50).…”
Section: Resultsmentioning
confidence: 92%
“…The hemC mutant will grow on solid media containing hemin but will not grow in liquid media containing hemin. This is reminiscent of the hemA mutant, AJB529, which shows very limited growth in broth containing hemin (49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lacZ transcriptional reporter used for assaying hemA expression contains a 1.4 kb insertion that has the 207th codon of hemA fused to lacZ. 10 The second step of the pathway involves the conversion of 5-aminolevulinic acid to porphobilinogen by the enzyme porphobilinogen synthase. hemB codes for this enzyme, and is separated by a 535 bp intergenic region from the divergently transcribed orf1148, which codes for a DNA helicase.…”
Section: Resultsmentioning
confidence: 99%
“…For example, hemA expression in R. capsulatus and in Rhodobacter sphaeroides is elevated slightly upon a shift from aerobic to anaerobic growth conditions. 10 It has been reported that the global RegA/RegB system is partly responsible for the regulation of hemA expression in R. sphaeroides. 11 Significantly more is known about regulating expression of the Mg-tetrapyrrole (bacteriochlorophyll) branch, as well as the regulation of apoproteins that bind heme and bacteriochlorophyll.…”
Section: Introductionmentioning
confidence: 99%